Optimized M/M/c model and simulation for bank queuing system - Yu-Bo Wang; Cheng Qian; Jin-De Cao (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
In this paper, a QuickPass model is proposed to improve bank queuing system based on queuing theory. The current bank queuing system is modeled with M/M/c and analytical approach is adopted to guide optimization strategy. Through adjusted greedy algorithm, the multiple-optimization model is simulated with MATLAB. Simulation result shows that the introduction of QuickPass system considerably reduces the average waiting time of customers both in regular queue and QuickPass queue. Pros and cons are analyzed and further application is discussed in the end.